Journalism Multiplatform environments: Entanglements, Looks and Reflections | DOI: 10.21204/2359-375X/ancora.v3n1p3-6 - NUNES, Pedro (2016)
In its fourth edition [V.3 N.1], the Latin-American Journalism - ANCHOR invites readers to reflect on the processes, practices and journalistic products, fueled by broad topic of discussion during the International Symposium on Journalism in multiplatform environments, held in November 2015, on the initiative of the Research Group in Journalism, Media, Accessibility and Citizenship - GJAC, linked to the graduate Program in Journalism UFPB, and the Research Group in Journalism and Mobility - MOBJOR of the State University of Paraiba.